2018
DOI: 10.1002/adfm.201706793
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Controlled Lysosomal Entrapment of Superparamagnetic Ferritin for Multimodal and Multiscale Imaging and Actuation with Low Tissue Attenuation

Abstract: Nanomaterials are of enormous value for biomedical applications because of their customizable features. However, the material properties of nanomaterials can be altered substantially by interactions with tissue thus making it important to assess them in the specific biological context to understand and tailor their effects. Here, a genetically controlled system is optimized for cellular uptake of superparamagnetic ferritin and subsequent trafficking to lysosomes. High local concentrations of photoabsorbing mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
0
13
2
Order By: Relevance
“…Fitting H C ( T ) yields an average blocking temperature T B which can be translated into K eff via 21· k B T ≈ K eff · V where k B the Boltzmann constant and V the NP volume. The prefactor 21 accounts for an attempt frequency of 10 9 Hz and the VSM measurement time of 1 s [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fitting H C ( T ) yields an average blocking temperature T B which can be translated into K eff via 21· k B T ≈ K eff · V where k B the Boltzmann constant and V the NP volume. The prefactor 21 accounts for an attempt frequency of 10 9 Hz and the VSM measurement time of 1 s [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…A semigenetic system used a genetic component, which interacted with exogenous components, which realized deep tissue imaging with genetic targetability [94]. It was previously reported that MFt was internalized into cells and subsequent trafficked to lysosomes through semigenetic approaches [79]. By controlling the expression of ferritin receptors, cells could uptake biosynthetic MFt and native ferrihydrite-containing ferritin, which accumulated in lysosomes.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The cobalt doping along with loss of crystallinity resulted in enhanced magnetic anisotropy, which was in conflict with the reported formation of antiferromagnetic Co 3 O 4 [55]. The semigenetic system, which allowed genetic targetability, enabled magnetic cell manipulation and cell ablation by photoablation or local magnetic hyperthermia [79]. Therefore, combining tumor imaging and tumor therapy is promising for practical applications, and different methods of cancer treatment may benefit from the use of MFt.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…MTT assay showed that 2 mM of free Epr, Epr-loaded HsAFr and HsAFr-Epr-FA diminish the cell growth up to 44 ± 5.1, 35 ± 3.32 and 26.66 ± 2.61 (%) respectively after 24 h, while after 72 h reduce the cell growth up to 35.33 ± 4.86, 25.83 ± 1.42 and 15 ± 4.6 (%), respectively. Higher toxicity of HsAFr-Epr-FA suggested, firstly, that the nanocarriers have high affinity for tumour cells due to their ability to bind FRs due to the presence of FA, and secondly the HsAFr can enter tumour cells through the interactions with scavenger receptor (SCARA5) and TfR1 overexpressed in the membranes of tumour cells [54]. H subunits are able to bind transferrin receptors while L subunits bind SCARA5 receptors [55].…”
Section: In Vitro Cytotoxicity Assaymentioning
confidence: 99%